2020
DOI: 10.2147/ott.s260215
|View full text |Cite
|
Sign up to set email alerts
|

<p>Aloperine Exerts Antitumor Effects on Bladder Cancer in vitro</p>

Abstract: Background: Human bladder cancer is the most common malignant tumor of the urinary system and one of the 10 most common tumors of the whole body. Although most patients with bladder cancer exhibit a good prognosis with standard treatment, effective therapies for patients with a recurrent or advanced bladder cancer are unavailable. Therefore, highly effective drugs to treat such patients need to be developed. Aloperine (ALO), a natural compound isolated from Sophora alopecuroides, has antitumor properties. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Studies revealed that ALO could reverse cisplatin resistance in colorectal cancer cells by inhibiting HIF-1α/ ERK pathway (Zheng et al, 2020). Moreover, ALO was reported to protect human epithelial cells against oxidative stress and apoptosis via regulating Nrf2/HO-1 signaling pathway (Zhang et al, 2020). In addition, ALO protected myocardial injury in rats via activation the PI3K/Akt pathway (Mao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that ALO could reverse cisplatin resistance in colorectal cancer cells by inhibiting HIF-1α/ ERK pathway (Zheng et al, 2020). Moreover, ALO was reported to protect human epithelial cells against oxidative stress and apoptosis via regulating Nrf2/HO-1 signaling pathway (Zhang et al, 2020). In addition, ALO protected myocardial injury in rats via activation the PI3K/Akt pathway (Mao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is crucial to develop effective antiviral drugs against ZIKV. Aloperine, known for its various pharmacological activities in treating cardiovascular diseases 22 and bladder cancer, 41 has emerged as a potential candidate for controlling viral infections. Recent studies have shown that aloperine can inhibit several viral infections, including hepatitis C virus (HCV), HIV‐1, and SARS‐CoV‐2 29,30,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer is the most common malignant tumor of the urinary system and is rated as the tenth most common form of cancer and the ninth leading cause of cancer-associated mortality worldwide in 2018, occurring in the mucous membrane of the bladder tissues (1,2). In china, its incidence ranks first among urogenital system tumors (3).…”
Section: Introductionmentioning
confidence: 99%